Biased or balanced? Assessing BBC news and current affairs performance in covering the badger cull in England. (January 2021) - Stanyer, James
Abstract: This article represents the first systematic examination of BBC coverage of one of the most controversial rural issues in a generation, namely the culling of badgers (a protected species) to stop the spread of bovine TB in England. While the BBC has certain regulatory responsibilities set out in its guidelines to provide duly impartial coverage it has been regularly criticised for being biased. Little is known about the BBC's performance other than what is suggested by critics, previous research having focused on press coverage. Based on an original content analysis of news, current affairs and factual output this article assesses the BBC's coverage. It shows that while competing voices and perspectives were balanced its coverage was not that distinct from its commercial rivals, with both framing the issue as a conflict over badgers rather than about the spread of a disease affecting livestock and livelihoods, and both focusing on a narrow set of voices involved in the conflict. Highlights: Systematic examination of bias in BBC coverage of the culling of badgers to stop the spread of bovine TB in England. No evidence of bias against certain rural communities, pursuits and businesses, nor failing to understand rural matters. Selected indicators did reveal coverage was problematic. BBC missed opportunities to broaden and contextualize the agenda, widen the selection of news actors, and challenge actor claims.